KLASIFIKASI JENIS BUNGA DENGAN MENGGUNAKAN CONVOLUTIONAL NEURAL NETWORK (CNN) - Fitriani Fitriani (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2021)
Flowers are an aesthetic component that is part of human life, in Indonesia there are many types of flowers, and each type has different characteristics, both in color and shape. In everyday life, people rarely know the type of flower so that many people often have difficulty determining the type of flower they see. This study aims to build a flower classification system using CNN for its classification. Convolutional neural network (CNN) is a type of deep learning algorithm that can determine any object in an image, recognize and distinguish one image from another. Based on the test scenarios carried out, the system can predict the type of interest with a probability accuracy value of 0.91.